2021
DOI: 10.18502/cjn.v20i1.6374
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D administration play a role in outcome of patients with acute ischemic stroke? A randomized controlled trial

Abstract: Background: Clinical studies have reported improved neurological outcomes in patients who were taking vitamin D supplements. This study investigates the effect of intramuscular (IM) vitamin D supplementation in patients with acute ischemic stroke (AIS) on neurological outcomes and inflammatory marker levels. Methods: This study included patients diagnosed with AIS (n = 60) from the Neurology Unit of Loghman Hakim Hospital, Tehran, Iran, during the year 2019. Patients with AIS were allocated randomly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Pada studi ini, didapatkan bahwa 7 artikel studi yang digunakan dalam evidence based case study ini menggunakan desain uji terkontrol acak atau randomized controlled trials (RCT) (Gupta et al, 2016;Hesami et al, 2022;Kadri et al, 2020;Karasu & Karataş, 2021;Narasimhan & Balasubramanian, 2017;Rezaei et al, 2021;Torrisi et al, 2021). Usia pasien yang terlibat dalam studi penelitian yang disertakan berkisar antara 18-80 tahun.…”
Section: Results Desain Dan Karakteristik Studiunclassified
See 3 more Smart Citations
“…Pada studi ini, didapatkan bahwa 7 artikel studi yang digunakan dalam evidence based case study ini menggunakan desain uji terkontrol acak atau randomized controlled trials (RCT) (Gupta et al, 2016;Hesami et al, 2022;Kadri et al, 2020;Karasu & Karataş, 2021;Narasimhan & Balasubramanian, 2017;Rezaei et al, 2021;Torrisi et al, 2021). Usia pasien yang terlibat dalam studi penelitian yang disertakan berkisar antara 18-80 tahun.…”
Section: Results Desain Dan Karakteristik Studiunclassified
“…Usia pasien yang terlibat dalam studi penelitian yang disertakan berkisar antara 18-80 tahun. Tipe diagnose medis stroke yang dimiliki oleh responden dalam studi penelitian yang disertakan yaitu sebanyak 5 studi hanya menyertakan pasien stroke iskemik sebagai responden penelitian (Gupta et al, 2016;Hesami et al, 2022;Kadri et al, 2020;Narasimhan & Balasubramanian, 2017;Rezaei et al, 2021) dan sebanyak 2 studi melibatkan pasien stroke iskemik dan hemoragik (Karasu & Karataş, 2021;Torrisi et al, 2021).…”
Section: Results Desain Dan Karakteristik Studiunclassified
See 2 more Smart Citations
“…The use of IM injection of single high-dose vitamin D in patients with ischemic stroke can be an appropriate treatment option in patients with poor compliance to daily oral vitamin D supplementation and could increase serum 25-OH vitamin D level rapidly and safely [ 16 ]. A few studies have examined the effect of high doses of vitamin D on the stroke severity and functional outcome scales of patients with ischemic stroke [ 17 , 18 , 31 ]. In accordance with our findings, Narasimhan et al and Sari et al revealed that a single dose, IM injection of 300000 to 600000 IU of vitamin D could improve functional outcomes of patients with ischemic stroke including Scandinavian Stroke Scale (SSS), mRS, NIHSS, and BI besides their balance [ 17 , 18 ], whereas Rezaei et al showed a single dose of 300000 IU IM vitamin D had no favorable effects on NIHSS score [ 31 ].…”
Section: Discussionmentioning
confidence: 99%